Factors influencing bone loss in anorexia nervosa: assessment and therapeutic options - Isabelle Legroux; Bernard Cortet (RMD Open)
Decreased mineral density is one of the major complications of anorexia nervosa. The phenomenon is even more pronounced when the disease occurs during adolescence and when the duration of amenorrhoea is long. The mechanisms underlying bone loss in anorexia are complex. Oestrogen deficiency has long been considered as the main factor, but cannot explain the phenomenon on its own. The essential role of nutrition-related factors—especially leptin and adiponectin—has been reported in recent studies. Therapeutic strategies to mitigate bone involvement in anorexia are still a matter for debate. Although resumption of menses and weight recovery appear to be essential, they are not always accompanied by a total reversal of bone loss. There are no studies in the literature demonstrating that oestrogen treatment is effective, and the best results seem to have been obtained with agents that induce bone formation—such as IGF-1—especially when associated with oestrogen. As such, bone management in anorexia remains difficult, hence, the importance of early detection and multidisciplinary follow-up.